(untitled) (Research, Society and Development, 2022)
The article discusses the representation of women in society in the first half of the 20th century in the Hollywood and Coisa Mais Linda series, broadcast over the internet on the Netflix streaming channel, set respectively in Los Angeles (USA) in the 1940s and Rio de Janeiro (BRA) in the 1950s-60s. The article aims to discuss gender, race and racism violence, using as methodology the analysis of productions from streaming channels that address topics that the mainstream media considers taboo. The role of the internet as a technology that assists in the dissemination of the possibilities for discussing a range of topics that would otherwise not be possible is indisputable. The woman is represented in the series of varied prisms, she is white, black, poor, rich. However, they have something in common: they are women and therefore suffer the same violence, both physical and symbolic. Gender and race violence are latent in the series. Discarding the concept of “truth”, the content of the works was used to talk about the foundations of colonialism and patriarchy (women as the property of men). The ideology that the woman belongs to the man supports this man’s supposed right to decide whether the woman lives or dies when she no longer wants to live with him. Netflix’s performance has enabled the discussion of diversity and individual rights in open dialogue with the general public. It is hoped that the article will contribute to broadening the discussion on gender and race equity in the educational and social field.